High Entropy Semiconductor AgMnGeSbTe4 with Desirable Thermoelectric Performance. (18th May 2021) - Ma, Zheng; Xu, Tian; Li, Wang; Cheng, Yiming; Li, Jinmeng; Zhang, Dan; Jiang, Qinghui; Luo, Yubo; Yang, Junyou
Abstract: A new p‐type high entropy semiconductor AgMnGeSbTe4 with a band gap of ≈0.28 eV is reported as a promising thermoelectric material. AgMnGeSbTe4 crystallizes in the rock‐salt NaCl structure with cations Ag, Mn, Ge, and Sb randomly disordered over the Na site. Thus, a strong lattice distortion forms from the large difference in the atomic radii of Ag, Mn, Ge, and Sb, resulting in a low lattice thermal conductivity of 0.54 W m −1  K −1 at 600 K. In addition, the AgMnGeSbTe4 exhibits a degenerate semiconductor behavior and a large average power factor of 10.36 µW cm −1  K −2 in the temperature range of 400–773 K. As a consequence, the AgMnGeSbTe4 has a peak figure of merit ( ZT ) of 1.05 at 773 K and a desirable average ZT value of 0.84 in the temperature range of 400–773 K. Moreover, the thermoelectric performance of AgMnGeSbTe4 can be further enhanced by precipitating of Ag8 GeTe6, which acts as extra scatting centers for holes with low energy and phonons with medium wavelength. The simultaneous optimization in power factor and lattice thermal conductivity yields a peak ZT of 1.27 at 773 K and an average ZT of 0.92 (400–773 K) in AgMnGeSbTe4 ‐1 mol% Ag8 GeTe6 . Abstract : A composite composed of AgMnSbGeTe4 and Ag8 GeTe6 shows promising thermoelectric performance; its peak ZT and average ZT are 1.27 (773 K) and 0.92 K (400–773 K), respectively. AgMnSbGeTe4 is a new high entropy semiconductor and crystallizes in the rock‐salt NaCl structure with cations Ag, Mn, Ge, and Sb randomly disordered over the Na sites.